(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper present experimental investigation results of common reeds (Phragmites australis) particle compacting in closed die. Common reeds are important natural biomass resource in Latvia. Compacting of biomass is very complicated process for solid biofuel production and there are many factors influencing to this process. The quality parameters of compacted biomass are described by European countries standards for solid biofuel. Density is the most important quality parameter of biomass compacting. The paper present results of common reeds particles compacting mechanism in closed die. Maximum pressure 212 MPa had been achieved in compacting. For compacting process evaluation has been determined pressing energy and density of briquettes. The minimum of density 0.87 g cm-3 have briquettes with particle size 12 – 13 mm, but maximum density 1.03 – 1.04 g cm-3 two particle sizes < 0.5 mm and 32 – 33 mm briquettes. Maximum value of energy consumption for compacting ( 172 kJ kg-1) has been obtained for reed particle size 32 – 33 mm, minimum value ( 53 kJ kg-1) for particle size less than 0.5 mm.